1408. Enterovirus D68 RNA Visualized in the Anterior Horn of the Spinal Cord of a Pediatric Patient with Flaccid Paralysis. (31st December 2020) - Vogt, Matthew R; Wright, Peter; Hickey, William; Crowe, James E; Boyd, Kelli
Abstract: Background: Acute flaccid myelitis (AFM) is a polio-like paralyzing illness of children. AFM incidence is increasing during every other year outbreaks that occur in the United States simultaneously with outbreaks of enterovirus D68 (EV-D68) infection. Demonstrating that EV-D68 directly causes AFM has been challenging due to rare detection of the virus in the cerebrospinal fluid (CSF) of patients despite frequent detection at nonsterile sites. Murine studies have shown that EV-D68 can infect spinal cord anterior horn motor neurons and cause paralysis, similar to poliovirus. However, a key outstanding question is whether EV-D68 causes AFM in humans by direct viral pathogenesis or by indirect host immunopathogenesis. Methods: We investigated the pathogenesis of AFM using tissues from a previously reported case of a 5-year-old boy who presented in fall 2008 with four days of progressive limb and voice weakness followed by incontinence, apnea, and death. He had a CSF pleocytosis of 2094/µL with EV-D68 identified in the CSF by sequencing of the VP1 gene. We designed probes for in situ hybridization (ISH) based on this sequence to stain formalin fixed paraffin embedded tissues from his autopsy. For immunohistochemistry (IHC) we used both commercial polyclonal anti-EV-D68 antibodies and our own human monoclonal antibodies that stain virus infected cells in vitro . Immunophenotyping was done by IHC. Results: With ISH we identified EV-D68 RNA in the anterior horn of the patient's spinal cord, corresponding to the location of motor neuron cell bodies. This area was highly inflamed, with an infiltrate of lymphocytes and macrophages. Viral RNA was in low abundance, and we could not detect viral surface proteins by IHC. Neither RNA nor viral antigen was detected in the lungs, which had extensive inflammatory infiltrate. Conclusion: Deaths in AFM patients are rare and often distant from initial presentation, but this patient died four days after onset of weakness, allowing us to directly demonstrate that EV-D68 can infect the human spinal cord. Low abundance of virus suggests the virus either reached the spinal cord prior to weakness onset or was cleared rapidly by the immune response. Therefore, both direct viral pathology and immune factors likely contribute to AFM disease in EV-D68 infection. Disclosures: James E. Crowe, Jr, MD, IDBiologics (Board Member, Consultant, Grant/Research Support)Vanderbilt University (Other Financial or Material Support, Inventor on patent related to this abstract)